Analisis Kompetensi Lulusan D4 Kebidanan FK UNPAD dengan Kebutuhan Dosen di Institusi D3 Kebidanan - Febrina Febrina (Lembaga Pengembangan Kinerja Dosen, 2024)
The graduate of midwifery D4 program is really needed in the institution to fulfill the needs to become the lecturing staff. This study is aimed to get to know the competency of the graduate midwifery D4 FK UNPAD with needed the lecture in midwifery D3 program. The method used in this study is the descriptive wih cross sectional approach. The number of sample is 89 respondents and 6 institution. The technique applied for the graduate of midwifery D4 FK UNPAD is purposive sampling technique. The result of this study that out of 89 graduates of midwifery D4 from FK UNPAD that are taken into the research, 83 respondent (93,25%) got the good competency according to the competency of midwifery D4 from FK UNPAD. And out of 6 (six) institution of midwifery D3 program that are taken into research, 5 (five) lecturing competency is needed in D3 midwifery institution. The conclusion of this study is that there is relevance between the competencies of graduates of midwifery D4 program FK UNPAD compared to the competency of the lecturer that is needed D3 midwifery program.